Highly active and stable Pt (111) catalysts synthesized by peptide assisted room temperature electron reduction for oxygen reduction reaction. (July 2016) - Wang, Wei; Wang, Zongyuan; Yang, Manman; Zhong, Chuan-Jian; Liu, Chang-Jun
Abstract: While carbon supported platinum (Pt) catalyst is the most effective and widely used cathode catalyst for oxygen reduction reaction (ORR) in proton exchange membrane fuel cells, the preparation of active and stable Pt catalysts remains challenging. In this work, we report a room temperature electron reduction method for the synthesis of a highly active and stable carbon supported Pt (111) catalyst under peptide assistance (Pt (111)-P/C). Such prepared catalyst shows surface sites featuring predominately (111) facets with particle size around 2 nm. In comparison with commercial Pt/C catalyst prepared by conventional methods, the mass activity and specific activity of the Pt (111)-P/C catalyst for ORR are shown to increase by a factor of 2. A 10, 000-cycle durability test of the Pt (111)-P/C catalyst has also showed a significantly enhanced stability over the commercial Pt/C catalyst. Graphical abstract: Highlights: The use of peptide and electron reduction leads to a nice size control of Pt NPs. The use of peptide and electron reduction makes the Pt surface predominately with (111) facets. The ORR activity of the electron reduced catalyst is two times higher than the commercial Pt/C catalyst. The stability of the electron reduced sample is significantly enhanced.